Two new species of the genus Zaitzeviaria Nomura, 1959 (Coleoptera: Elmidae) from China - Jiang, Ri-Xin; Chen, Xiang-Sheng (Zootaxa, 2025)
Two new species of the genus Zaitzeviaria Nomura, 1959 are described and figured from Southwest China: Zaitzeviaria chenzhitengi sp. nov. from Yunnan Province and Zaitzeviaria guiyangensis sp. nov. from Guizhou Province. A key to Chinese Zaitzeviaria species is provided.